Sejarah Perkembangan Ilmu Hadits dan Kelompok Ingkar Sunnah - Abdul Karim, Mohamad Aqbil Wikarya; Avicena, Muhamad Zaky; Ahmad, Nurwadjah; Yuda, Dendi; Arsyad, M Fikri; Nurcahya, Yan; Oksa Putra, M Zikril (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This article examines the development of the science of hadith as a crucial pillar in Islamic scholarly tradition and the emergence of the Qur’anists (commonly referred to as Ingkar Sunnah), who reject the authority of hadith as a source of Islamic law and teachings. The study explores the historical evolution of hadith science from the time of Prophet Muhammad (PBUH) to the contemporary era, including the establishment of methodologies for sanad (chain of transmission) and matan (content) criticism, as well as the role of scholars in preserving the authenticity of hadith. On the other hand, the article analyzes the thoughts and arguments of Qur’anists, focusing on their historical background, factors contributing to their spread, and the ideological and practical implications of their rejection of hadith. Using a qualitative approach based on literature review, the article finds that the development of hadith science has significantly contributed to safeguarding the authenticity of Islamic tradition, while the Qur’anist movement often arises as a response to specific social, political, and intellectual dynamics. This study highlights the importance of scholarly dialogue and comprehensive education in addressing the challenges posed by this group, while reinforcing the appreciation of hadith science as an integral part of Islamic intellectual heritage.